2014
DOI: 10.1037/a0036302
|View full text |Cite
|
Sign up to set email alerts
|

Age-related and death-related differences in emotional complexity.

Abstract: The present study aimed to examine an aspect of emotional complexity as seen in covariation between retrospective judgments of positive and negative affects. We assume that individuals can experience positive affect independently of negative affect. Theories argue that emotional complexity increases in old age, but research shows mixed evidence. Additionally, emotional complexity has been shown to decrease in situations prevalent in old age, such as physical illness and disability. Integrating distinct effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 70 publications
2
18
0
1
Order By: Relevance
“…The former finding is in line with most of the previous studies that generally failed to find an association between age and various measures of emotional complexity (Gr€ uhn et al, 2013;Ong & Bergeman, 2004;Palgi et al, 2014;Ready et al, 2008, study 1;Ready et al, 2012). The latter finding accords with the multi-sample study that found a decreased co-occurrence of retrospective ratings of PA and NA among those perceiving death as close .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The former finding is in line with most of the previous studies that generally failed to find an association between age and various measures of emotional complexity (Gr€ uhn et al, 2013;Ong & Bergeman, 2004;Palgi et al, 2014;Ready et al, 2008, study 1;Ready et al, 2012). The latter finding accords with the multi-sample study that found a decreased co-occurrence of retrospective ratings of PA and NA among those perceiving death as close .…”
Section: Discussionsupporting
confidence: 93%
“…Covariates included gender, education [ranging on a scale from 0 (no formal education) to 5 (academic education)], marital status, and subjective health, as these were found to be related to age and subjective DtD (Griffin, Loh, & Hesketh, 2013;Palgi et al, 2014;Shrira et al, 2014), and we were interested in examining the effects of age and subjective DtD after adjusting for possible effects of other background characteristics. Subjective health was assessed with a single question ('As a whole, how do you rate your health?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, core deficits in informaton processing, including higher levels of cognitive simplicity [42, 40], neuroticsm [25, 23], hostility [45] and lower levels of mood clarity [43], trait PA [57], psychological resilience [47], and subjective perceptions of approaching death [58] have all been implicated as factors that increase vulnerability to affective simplification during times of stress. Overall, the available evidence suggests that individual differences, especially those that have relevance for differentiation of emotional experience, warrant further investigation as potential moderators of the interplay between PA and NA.…”
Section: The Dynamic Model Of Affectmentioning
confidence: 99%